An RDE Investigation of NaOH Effect on Electrosynthesis of Lead Dioxide in Alkaline Solution. Issue 7 (2nd April 2016) - He, Shiwei; Xu, Ruidong; Han, Sha; Wang, Jiong; Chen, Buming
Abstract : An electrochemical investigation of NaOH concentration on electrosynthesis of lead dioxide in alkaline solutions was performed using rotating disk electrodes (RDE). The results show that Pb(II) does not modify the evolution of oxygen in alkaline solutions, and the reaction taking place at 0.84 VSHE is under the mixed control of ionic transport and charge transfer. The Koutechy-Levich equation was used to calculate the value of diffusion coefficient D and apparent heterogeneous rate constant k of the PbO2 electrodeposition process at 0.84 VSHE . The results indicate that NaOH has a negative influence on the diffusion of Pb(II) within a NaOH concentration range of 2.5 ∼ 4.5 M. In addition, NaOH has a positive influence on the apparent heterogeneous rate constant of Pb(II) oxidation reactions within a NaOH concentration range of 2.5 ∼ 3 M, but a negative influence within a NaOH concentration range of 3 ∼ 4.5 M. XRD and SEM were employed to investigate the effects of NaOH concentration on phase composition and surface microstructures of deposits. The results show that PbO2 synthesized in an alkaline solution consists of pure α phase. The deposits are all composed of rounded nanocrystallites, except for the deposit synthesized in a solution of 3 M NaOH, which exhibited rod-like crystallite.